106 "The medical electives suitcase": an essential tool for medical students. (17th November 2016) - Woods, A; Maweni, R; Kuhurt, K; Holm, V; Vig, S; Alexander, D; Foley, R
Abstract : Medical electives are an important and longstanding part of a medical student's education, allowing exposure to a new range of medical conditions, health beliefs and health systems. Electives provide unique ethical and clinical challenges that are often not covered in their core curriculum. We surveyed medical students and junior doctors in the UK and Republic of Ireland about their elective experiences, most students travelled outside the British Isles (84%) and over half (56%) reported carrying out one or more clinical procedures they felt uncomfortable with. We felt our survey highlighted a clear learning need and developed a course designed to help bridge the gap between theory and practice. The "Medical Electives Suitcase" combines workshops, small group practical skills sessions and immersive simulation scenarios. Our aims were to: Highlight the important and common ethical issues students may face and give them a reflective framework to consider when in situ Raise awareness of non-technical skills Improve confidence and competence in a variety of clinical procedure skills Improve clinical knowledge and confidence when assessing unwell patients in unfamiliar environments. How we achieved this: Ethics: Tutorial and facilitated interactive workshop, discussing in small groups issues of consent, research ethics, professionalism and professional probity. Non-technical skills: Interactive Human Factors discussion exploring challenges of leadership, team working and situational awareness in healthcare settings. Key communication factors such as language barriers, team-working and handover were built into simulation scenarios. Clinical procedure skills: Small group skills workshops using part-task trainers covering venepuncture, cannulas, IV fluid administration, suturing and urinary catheterisation. Assessment and management of unwell patients: Simulation scenarios using both high fidelity mannequins and actors covering emergencies in medicine (sepsis), obstetrics (pre-eclampsia), paediatrics (resuscitation) and surgery (bleeding). We have run the course twice now for students across London and had enthusiastic and positive feedback